Impact of carprofen administration on stress and nociception responses of calves to cautery dehorning. Issue 2 (1st February 2016) - Stock, M. L.; Barth, L. A.; Van Engen, N. K.; Millman, S. T.; Gehring, R.; Wang, C.; Voris, E. A.; Wulf, L. W.; Labeur, Léa; Hsu, W. H.; Coetzee, J. F.
Abstract: The objective of this study was to investigate the effects of carprofen administered immediately before cautery dehorning on nociception and stress. Forty Holstein calves aged approximately 6 to 8 wk old were either placebo treated and sham dehorned ( n = 10) or cautery dehorned following administration of carprofen (1.4 mg/kg) subcutaneously ( n = 10) or orally ( n = 10) or a subcutaneous and oral placebo ( n = 10) in a randomized, controlled trial. All animals were given a cornual nerve block using lidocaine before dehorning. Response variables including mechanical nociception threshold, ocular temperature, heart rate, and respiratory rate were measured before and following cautery dehorning for 96 h. Blood samples were also collected over 96 h following dehorning and analyzed for plasma cortisol and substance P concentrations by RIA. Plasma carprofen concentration and ex vivo PGE2 concentrations were also determined for this time period. Average daily gain was calculated for 7 d after dehorning. Data were analyzed using a linear mixed effects model with repeated measures, controlling for baseline values by their inclusion as a covariate in addition to planned contrasts. Dehorning was associated with decreased nociception thresholds throughout the study and a stress response immediately after dehorning, following the loss of local anesthesia, and 48 h after dehorning compared with sham-dehorned calves. Carprofen was well absorbed after administration and reached concentrations that inhibited ex vivo PGE2 concentrations for 72 h (subcutaneous) and 96 h (oral) compared with placebo-treated calves ( P < 0.05). Carprofen-treated calves tended to be less sensitive ( P = 0.097) to nociceptive threshold tests. Overall, at the dosing regimen studied, the effect of carprofen on sensitivity and stress following cautery dehorning was minimal. Consideration of route of administration and dose determination studies may be warranted.